Perspective on the Road toward Gene Therapy for Parkinson’s Disease - Blits, Bas; Petry, Harald (Frontiers in Neuroanatomy, 2017)
Many therapeutic strategies aimed at relieving symptoms of Parkinson’s disease (PD) are currently used for treatment of this disease. With a hallmark of progressive degeneration of dopaminergic neurons, the absence of properly operational dopaminergic circuitry becomes a therapeutic target. Following diagnosis, dopamine replacement can be given in the form of L-DOPA (L-3,4-dihydroxyphenylalanine). Even though it is recognized as standard of care, this treatment strategy does not prevent the affected neurons from degenerating. Therefore, studies have been performed using gene therapy (GT) to make dopamine (DA) available from within the brain using an artificial DA circuitry. One approach is to administer a gene therapy aimed at delivering the key enzymes for dopamine synthesis using a lentiviral vector system (Palfi et al., 2014). A similar approach has been investigated with AAV (adeno-associated virus) expressing aromatic L-amino acid decarboxylase (AADC), tyrosine hydroxylase (TH) and GTP-cyclohydrolase I (GCH) (Bankiewicz et al., 2000), which are downregulated in PD. Another GT approach to mitigate symptoms of PD used AAV-mediated delivery of GAD-67 (glutamate decarboxylase) (Kaplitt et al., 2007). This approach mimics the inhibitory effect of DA neurons on their targets, in reducing motor abnormalities. Finally, disease modifying strategies have been undertaken using neurotrophic factors such as Neurteurin (NTN) (Marks et al., 2007, Bartus et al., 2013) or are ongoing with the closely related Glial cell line-derived neurotrophic factor (GDNF). Those approaches are aiming at rescuing the degenerating neurons. All of the above mentioned strategies have their own merits, but also some disadvantages. So far, none of clinical applied GT studies has resulted in significant clinical benefit, although some clinical studies are ongoing and results are expected over the next few years.